2016
DOI: 10.1542/peds.2016-3022
|View full text |Cite
|
Sign up to set email alerts
|

Youth Participation and Injury Risk in Martial Arts

Abstract: The martial arts can provide children and adolescents with vigorous levels of physical exercise that can improve overall physical fitness. The various types of martial arts encompass noncontact basic forms and techniques that may have a lower relative risk of injury. Contact-based sparring with competitive training and bouts have a higher risk of injury. This clinical report describes important techniques and movement patterns in several types of martial arts and reviews frequently reported injuries encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 45 publications
0
23
0
6
Order By: Relevance
“…Despite the mandatory use of protective hand gear in both training and competition this study underlines that relying on gear alone cannot prevent severe injuries caused by excessive forces deriving from attacking punches and blocking of foot kicks [25,[27][28][29]. To prevent ongoing rise in injuries in Olympic taekwondo athletes coaches should put emphasis on technical skills even under physiological and psychological stress during training as recommended before [30].…”
Section: Discussionmentioning
confidence: 90%
“…Despite the mandatory use of protective hand gear in both training and competition this study underlines that relying on gear alone cannot prevent severe injuries caused by excessive forces deriving from attacking punches and blocking of foot kicks [25,[27][28][29]. To prevent ongoing rise in injuries in Olympic taekwondo athletes coaches should put emphasis on technical skills even under physiological and psychological stress during training as recommended before [30].…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to these findings, Curran-Sills and Abedin [ 30 ] reported that MMA does not confer the same exposure to concussion over a 10-year period as seen in other popular sports (e.g., ice hockey, American football, rugby union), but it is important to avoid this simplified derivation because of methodological differences across the studies [ 30 ]. A recent study found that head injuries dominate in MMA [ 23 , 30 , 31 , 32 , 33 ]. Professional mixed martial artists (MMA fighters) as such boxers are at risk of sustaining acute head and neck injury each time they engage in practice or competition [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AAP's assertion that consent is sufficient to justify participation in youth tackle football appears to be inconsistent with AAP policy statements on at least 5 other sports and activities. [37][38][39][40] We will focus on hockey.…”
Section: The Aap's Football Policy Is Inconsistent With Aap Policy Onmentioning
confidence: 99%